Management of hazardous waste from mining to mitigate adverse environmental impact in the La Libertad Region (SCIÉNDO INGENIUM, 2025)
This study proposes a management model aimed at reducing the environmental impact caused by hazardous waste generated by mining activities in the La Libertad region. The approach used is both descriptive and analytical, based on a detailed analysis of the available literature. An inventory of mining companies was compiled, and the types of waste generated were characterized, ranging from sterile to industrial waste. Using a cause-and-effect matrix, environmental impacts were assessed, resulting in a Hazardous Waste Management Plan that includes strategies for waste minimization, treatment, and final disposal, validated by experts. Although companies operate within a formal framework, improper waste management remains a challenge. It is concluded that it is crucial to implement minimization alternatives from the source of waste generation to protect the natural environment and nearby communities. The effective implementation of the proposed management model will contribute to the evaluation of hazardous waste and foster greater environmental responsibility in the mining sector, ensuring the preservation of ecosystems and safeguarding the health of surrounding communities.
Keywords: Hazardous waste; environmental impact; assessment